Loan workouts and debt for equity swaps: a framework for successful corporate rescues - Chatterji, Subhrendu; Hedges, Paul. (Chichester [UK] ; New York : Wiley, 2001)
The book provides a practical guide to the entire range of issues and a framework for methodical, step by step approach to loan workouts.
Series statement taken from jacket.
Includes bibliographical references and index.
uaj 10/04/2015
Loan
Keywords: Corporations -- Finance; Corporate reorganizations; Corporate debt; Corporate turnarounds